Réponses

2013-12-17T18:47:14+01:00
A= -2(x+6)+5(x+4)
 = (-2 x x +(-2) x 6) + (5 x x + 5 x 4)
 = -2x + (-12) + 5x + 20
 = -2x + 5x -12 + 20
 = 3x + 8

 b=4(xau carre -8) -7 (3- x au carre)
   =( 4 x xau carre - 4 x 8) - ( 7 x 3 - 7 x xau carre)
   = 4xau carre - 32 - 21 + 7xau carre
   = 4xau carre + 7xau carre - 32 - 21
   = 11xau carre -53

c= -5 (4- xau carre) - 6 (5-2xaucarre)
  = ( -5 x 4 -5 x xau carre) - ( 6 x 5 - 6 x 2xau carre)
  = -20 -5xau carre -30 + 12xau carre
  = -20-30 -5xau carre + 12xau carre
  = -50 + 7xau carre
 
d= 3x (4x+5) -7 ( xau carre-1)
  = ( 3x x 4x + 3x x 5 ) - ( 7 x xau carre - 7 x 1)
  = 13xau carre + 15x - 7xau carre - 7
  = 13xau carre - 7xau carre + 15 - 7
  = 6xau carre -8
2013-12-17T18:54:58+01:00
1)a= -2(x +6) +5 (x+4)
a= - 2x -12 + 5x + 20 = 3x + 8
2)b=4(xau caree -8) -7 (3- x au carre)
b= 4 (x²-8) - 7 ( 3- x²) = 4x² - 32 - 21 + 7 x² = 11x² - 53
3)c= -5 (4 - x au carre) -6 (5-2xau carre) = -5 (4- x²) -6 (5- 2x²)
c= -20 + 5x² -30 + 12 x² = 17 x² - 50
4)d= 3x (4x +5) -7 (x au carre -1)=  3x (4x +5) -7(x²-1) = 12 x² + 15x - 7x² + 7 = 5 x² +15x +7 = 5x (x+3) +7